2016 International Conference on Computer and Communication Engineering (ICCCE) 2016
DOI: 10.1109/iccce.2016.72
|View full text |Cite
|
Sign up to set email alerts
|

Development of Particle Swarm Optimization Based Rainfall-Runoff Prediction Model for Pahang River, Pekan

Abstract: Flooding is a natural disaster which has been occurring annually throughout the whole world. The disaster, such as other natural catastrophe could only be mitigated rather than it being completely solved. Runoff prediction proved to be very vital in pre-flooding management system. In recent years, Artificial Neural Network has been applied in various prediction models of hydrological system. It is proposed to model the rainfall-runoff system of Pahang River in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Camera based wayfinding techniques include SLAM [36], Microsoft Kinect [37]- [39], novel liquid sound navigation [40] and FL2-0352 camera [41]. Machine learning methods which are getting numerous attention for researchers nowadays [42], [43] such as particle swarm optimization (PSO) [44] have also been implemented for navigation purposes. [16], [27], [36], [40], [45] [24], [ 25], [27], [46] [30], [32], [33]…”
Section: Discussion On Navigation Techniquesmentioning
confidence: 99%
“…Camera based wayfinding techniques include SLAM [36], Microsoft Kinect [37]- [39], novel liquid sound navigation [40] and FL2-0352 camera [41]. Machine learning methods which are getting numerous attention for researchers nowadays [42], [43] such as particle swarm optimization (PSO) [44] have also been implemented for navigation purposes. [16], [27], [36], [40], [45] [24], [ 25], [27], [46] [30], [32], [33]…”
Section: Discussion On Navigation Techniquesmentioning
confidence: 99%
“…A funnel was shaped by the optimization technique. Therefore, it was concluded that overflow and drainage of water model can be investigated by applying PSO with huge data size in very less processing time [36]. Early identification can be considered as the most important factor for the breast cancer affected woman.…”
Section: B Artificial Intelligence Based Methodsmentioning
confidence: 99%
“…The foundation of Particle Swarm Optimization (PSO) can be represented as a bunch of random particles (solutions) which have their own random position and velocities. With the particles flowing over the hyperspace searching for possible solutions, a search for optima over a series of iteration was completed [47]. The particles learning process is based on its own experience and other particle's prior experience.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%